Effect of CaO and ZnO Additions on Density, Electrical, and Thermal Properties of Gd-Doped Ceria - G. Martínez-De la Rosa; J.A. Díaz-Guillén; O.J. Durá; M.E. Bazaldúa-Medellín; O. Burciaga-Díaz; K.P. Padmasree (Materials Research)
The effects of CaO and ZnO as sintering aids on the electrical and thermal properties of Gd-doped CeO2 ceramics were investigated. Different systems of general formulas Gd0.1Ce0.9O1.95 and A0.02Gd0.08Ce0.9O1.94 (where A = Ca and Zn) were obtained by mechanochemistry, with a maximum milling time of 20 h. XRD analysis of synthesized samples revealed pure phases with a fluorite-type structure, derived from the CeO2 cubic system. Heat treatments from 800 to 1500°C enhanced crystallinity and confirmed the formation of the solid solution. SEM studies of samples sintered at 1200 and 1350°C showed similar characteristics across all systems. Both CaO and ZnO improved the materials’ relative density (~95%) at a sintering temperature of 1200 °C. Impedance spectroscopy demonstrated that the sintering aids did not have an adverse effect on ionic conductivity at 650°C, while thermal conductivity tended to decrease as the temperature increased, aligning with density results.